A supramolecular gel based on a glycosylated amino acid derivative with the properties of gel to crystal transition. Issue 1 (8th October 2015) - Liu, Jie; Xu, Fengyang; Sun, Ziling; Pan, Yue; Tian, Jian; Lin, Hsin-Chieh; Li, Xinming
Abstract : A novel gelator from a glycoamino acid derivative was discovered to perform supramolecular self-assembly and gel–crystal transition upon ageing. Abstract : Here we report the generation of a novel gelator from a glycosylated amino acid derivative, which contained three structural units, an aromatic residue, a carbohydrate moiety and a tert -butyl group in a single molecule. These structural units can promote the supramolecular self-assembly of this gelator in both aprotic and protic solvents via coordinated π–π stacking, multiple hydrogen binding and van der Waals interactions. More importantly, due to their non-equilibrium natures, the organogels formed in DCM, chloroform and ethanol can undergo gel to crystal transition in storage, driven by unbalanced gelator–gelator and solvent–gelator interactions. In this process, the gelators were firstly trapped in a kinetically favorable gel state, and then transferred into a more thermodynamically stable crystal state upon ageing, with the generation of microcrystals in different morphologies.